BIOETHANOL PRODUCTION VIA SYNGAS FERMENTATION OF CLOSTRIDIUM LJUNGDAHLII USING HOLLOW FIBER MEMBRANE SUPPORTED BIOREACTOR - Keryanti
Lignocellulosic waste has the potential as a renewable energy source to produce biofuels, a substitute for fossil fuels whose supplies are limited and also cause environmental pollution problems. Gasification of lignocellulosic biomass followed by syngas fermentation can produce biofuels such as bioethanol. However, syngas fermentation still has challenges such as gas-liquid mass transfer limitation and low productivity. Therefore, process development including appropriate selection of reactor design, configuration, and operating conditions are required to improve the performance of syngas fermentation process. The purpose of this study was to evaluate the performance of hollow fiber membrane (HFM) as a reactor configuration for syngas fermentation. The membrane reactor system is connected to a reservoir tank for liquid recirculation. The volumetric mass transfer coefficient (KLa) of the HFM reactor was determined at abiotic conditions using air. The HFM reactor configuration was operated for syngas fermentation by Clostridium ljungdahlii at different operational conditions, including the syngas flow rate and liquid recirculation between the module and reservoir. Performance of the reactor system was evaluated on cell growth, the rate of syngas consumption, and the productivity of ethanol. This study results higher KLa value of HFM reactor than reactor without membrane system. Compared with reactor without membrane, bioethanol productivity at HFM reactor configuration has three times higher maximum concentration of 2,7 g/L with an ethanol to acetic acid ratio of 2,32. At HFMR configuration, fermentation performances increased with the increasing of syngas flowrate and media recirculation rate until the reaction wasn’t mass transfer limited; instead, the rate-limiting step might be the kinetic growth. At general, the research shows the configuration of HFM reactor is an efficient reactor system for syngas fermentation.